Respuesta :

[tex]\longrightarrow{\blue{ 0 }}[/tex] 

[tex]\sf \bf {\boxed {\mathbb {STEP-BY-STEP\:EXPLANATION:}}}[/tex]

[tex]7 - ( \frac{5}{6} \times 7) - \frac{7}{6} [/tex]

[tex] = 7 - \frac{35}{6} - \frac{7}{6} [/tex]

Since the denominators are unequal, we find the L.C.M (lowest common multiple) for the denominators.

The L. C. M is 6.

Now, multiply the L.C.M. with both numerator & denominator.

[tex] = \frac{7 \times 6}{1 \times 6} - \frac{35}{6} - \frac{7}{6} [/tex]

Now that the denominators are equal, we can add/subtract them.

[tex] = \frac{42- 35 - 7}{6} [/tex]

[tex] = \frac{42 - 42}{6} [/tex]

[tex] = \frac{ 0}{6} [/tex]

[tex] = 0[/tex]

[tex]\red{\large\qquad \qquad \underline{ \pmb{{ \mathbb{ \maltese \: \: Mystique35♛}}}}}[/tex]